COMMISSIVE SPEECH ACTS IN THE FIRST PUBLIC DEBATE OF THE 2024 RIAU GUBERNATORIAL CANDIDATES: A PRAGMATIC ANALYSIS - Fitri, Fadillah; Asnawi, Asnawi (JURNAL KONFIKS, 2025)
The first public debate of the 2024 Riau gubernatorial election is a significant political and linguistic event, where candidates utilize the debate platform to construct political credibility through discursive strategies. This study aims to describe and analyze the forms of commissive illocutionary speech acts, particularly promises, used by candidates during the debate. The focus is on identifying verbal commitments as indicators of future policy intentions. This research employs a qualitative-descriptive approach, with the primary data sourced from a 1-hour-59-minute debate video broadcast by Kompas TV. Data were collected through documentation and transcription methods, and analyzed using Searle’s (1969) speech act theory, specifically the commissive category. The data analysis followed the Miles Huberman model through stages of reduction, display, and verification. The findings reveal that commissive speech acts, especially promises, dominate the candidates' communication strategies and fall into three thematic domains: (1) infrastructure technology development, (2) improving welfare poverty alleviation, and (3) governance education integrity. Candidates frequently employ futuristic verbs such as “will” and “intend” as rhetorical tools to establish public trust. This study contributes to the field of political pragmatics and language literacy, especially in the context of regional political debates. However, the study is limited by its focus on a single debate session, without examining post-election promise fulfillment. Future research is encouraged to explore the gap between political utterances and policy implementation.